Meningkatkan Motivasi Belajar dengan Penggunaan Vidio Pembelajaran di MtsS Asy-Syarif Sidang Koto Laweh - Melani Melani; Fadhilla Yusri; Leli Adriyanti (Badan Penerbit STIEPARI Press, 2024)
In the modern era of education. The use of learning videos is becoming an important aspect in increasing students' motivation and effectiveness in learning. Educational research and practice shows that learning videos have great potential to positively influence learning motivation for students, and this has become a focus of attention in the world of education. This abstract will explain a number of factors and the impact of using learning videos on student motivation. The use of learning videos opens the door to a more interesting and memorable learning experience for students. Students will tend to be more active in the learning process when presented with relevant and interesting videos. This makes students have increasing motivation within themselves. Apart from that, the use of learning videos varies in learning methods by using various kinds of videos, including the use of animations, documentaries, or presentations which can be used to meet students' various ways of learning.